PTU-184 Defining and treating a positive circumferential resection margin in oesophageal and gastro-oesophageal junctional cancer. (28th May 2012) - O'Neill, J R; Stephens, N; Save, V; Phillips, H; Kamel, H M; Robertson, A G; Driscoll, P J; Paterson-Brown, S
Abstract : Introduction: A positive circumferential resection margin (CRM) has been implicated with poorer prognosis in oesophageal and gastro-oesophageal junctional (OGJ) cancer. The Royal College of Pathologists (RCP) defines a margin as positive if tumour cells are present within 1 mm. In contrast, the College of American Pathologists (CAP) only defines a margin as positive if tumour cells are observed at the margin. The equivalence of the systems is not clear and the impact of adjuvant treatment has not been assessed. Aims: To compare the prognostic ability of the RCP and CAP systems in a cohort from a single UK centre and to determine if adjuvant radiotherapy offers a survival benefit for CRM positive patients. Methods: Patients with a "T3" adenocarcinoma or squamous cell carcinoma of the oesophagus or OGJ undergoing potentially curative resection between 1994 and 2010 were identified from a prospective database. Resection specimens were reviewed and the CRM was measured to ± 0.1 mm by a consultant pathologist. Univariate, multivariate and propensity score matching analyses (PSMA) were performed. Results: A total of 226 patients were included. Cox regression demonstrated patient sex (p=0.009), tumour differentiation (p=0.015), nodal (N) stage (p<0.001) and CRM group (p=0.045) were independently predictive of prognosis. Patients were grouped into CRM of 0 mm (CAP+ve, n=47), CRM >0 mm but <1 mm (RCPCRM, n=83) and CRM ≥1 mm (CRM-ve, n=96). Median survivals (95% CIs) were significantly different across groups (p=0.019) with CAP+ve = 18 months (13.0 to 23.0), RCPCRM = 28 months (18.6 to 37.3) and CRM-ve = 33 months (25.8 to 40.2). A trend for poorer survival was noted for the CAP+ve vs the RCPCRM group (p=0.073) although there was heterogeneity in N stage across groups. PSMA demonstrated no residual survival difference between CAP+ve and RCPCRM groups when other prognostic variables were controlled. Significant selection bias was observed for patients undergoing adjuvant radiotherapy. PSMA was applied to assess the treatment effect. Patients undergoing adjuvant radiotherapy (n=23) showed significantly improved survival when compared to controls (n=23) matched for sex, pre-operative treatment, N stage, histology and differentiation (p=0.04). Conclusion: The survival difference between CAP+ve and RCPCRM groups could be explained by existing prognostic variables. The CAP and RCP systems therefore appear equivalent in our cohort. In selected patients with a CRM <1 mm, adjuvant radiotherapy may be of benefit and a prospective randomised trial is indicated. Competing interests: None declared.